3-D thermal analysis and contact resistance evaluation of power cable joint. (25th January 2016) - Yang, Fan; Cheng, Peng; Luo, Hanwu; Yang, Yongming; Liu, Haibo; Kang, Kai
Highlights: A 3-D electromagnetic-thermal model for power cable joint was set up. The influence of contact resistance on temperature was taken into consideration. The influence rules of k, I and Tamb on cable temperature were investigated. A mathematical method to evaluate the contact resistance was developed. Abstract: Aiming at the overheating problem of power cable joints, which is mainly caused by great contact resistance and unqualified installation, a 3-D electromagnetic-thermal model for power cable joint was set up, and a method was presented to deal with the influence on the thermal distribution of power cable joint caused by the contact resistance RJ . Example calculation was described in details, and the result shows that the cable conductor temperature along the axial direction exponentially decreases within the range of 2 m away from the cable joint center. The numerical results agreed with the analytical results and measured results within 5%. Then the influence rules of contact coefficient k, ambient temperature Tamb and load current I on cable joint thermal distribution were investigated. Finally, the piecewise functions of the cable temperature difference Δ T, k and I were developed to evaluate the RJ of the power cable joint by regression analysis, which can be used to evaluate whether a power cable joint is qualified or not, and the correlation coefficients are greater than 0.999. Results indicate that to ensure the lower conductor temperature of cable joint than that of cable body, the k should be less than 2.7, and the relative error between the proposed evaluation method and the simulation method is within 2%.